Personal Styles in Early Cycladic Sculpture - Getz-Gentle, Pat (Book collections on Project MUSE., 2001)
"Personal Styles in Early Cycladic Sculpture represents the culmination of thirty-five years of study. Pat Getz-Gentle offers here much new material and many fresh insights into a tradition, rooted in the Neolithic period, that spanned most of the third millennium B.C. She begins with a review of this tradition, placing particular emphasis on the stages leading to the reclining figure with folded arms that is the unique and quintessential icon of the early Bronze Age culture at the center of the Aegean. She then focuses on the styles of fifteen sculptors, several of whom are identified and discussed for the first time in this volume. By introducing little-known pieces attributable to these sculptors, she illuminates various phases of their artistic development."--Jacket